2014
DOI: 10.1371/journal.pone.0101798
|View full text |Cite
|
Sign up to set email alerts
|

How Many Wolves (Canis lupus) Fit into Germany? The Role of Assumptions in Predictive Rule-Based Habitat Models for Habitat Generalists

Abstract: Due to legislative protection, many species, including large carnivores, are currently recolonizing Europe. To address the impending human-wildlife conflicts in advance, predictive habitat models can be used to determine potentially suitable habitat and areas likely to be recolonized. As field data are often limited, quantitative rule based models or the extrapolation of results from other studies are often the techniques of choice. Using the wolf (Canis lupus) in Germany as a model for habitat generalists, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 52 publications
2
31
0
2
Order By: Relevance
“…Consequently, during the construction of a HSM for wolves it is essential to distinguish between predictors of areas with just a general presence of the species, including floaters, and the permanent range of the species, where they can establish territories (Marucco & McIntire, ). Models based on observations of solitary wolves wandering in search of mates and free territories, especially if such data included, for example, media reports, may provide inconclusive results (Fechter & Storch, ). Also Cianfrani et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, during the construction of a HSM for wolves it is essential to distinguish between predictors of areas with just a general presence of the species, including floaters, and the permanent range of the species, where they can establish territories (Marucco & McIntire, ). Models based on observations of solitary wolves wandering in search of mates and free territories, especially if such data included, for example, media reports, may provide inconclusive results (Fechter & Storch, ). Also Cianfrani et al.…”
Section: Discussionmentioning
confidence: 99%
“…Across their geographic range, wolves inhabit different environments: tundra, boreal and temperate forests, steppes and semi‐deserts, and habitats transformed by humans to varying degrees (Mech & Boitani, ). Therefore, the predictive power of HSMs for wolves has been hotly debated (Fechter & Storch, ; Mech, ,b; Mladenoff, Clayton, Sickley, & Wydeven, ). However, while some authors doubt the predictive power of HSMs for wolves (Cayuela, ; Mech, ), others have revealed environmental factors that support or hamper wolf occurrence (Kaartinen, Kojola, & Colpaert, ; Llaneza, López‐Bao, & Sazatornil, ; Thiel, ; Thurber, Peterson, Drummer, & Thomasma, ; Wydeven et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Several qualifications are necessary, however, to properly understand the European situation and how that relates to wolf recolonization of the 48 contiguous United States (Mech, 2016).First, the high human densities in Europe are mostly in cities, so any wolf conflict is borne by the sparse populations in the countryside.Most European wolves inhabit Spain, Italy and such countries as Greece, Romania, Bulgaria, whereas wolves have only recently begun to recolonize the wealthier nations such as Germany (Fechter and Storch, 2014).Thus the average European human density as cited by Chapron et al (2014) is not a suitable metric by which to gauge wolf compatibility with humans.Second, several of the countries supporting the highest number of wolves attempt to control them by hunting (Boitani, 2003), including Sweden, which is in open violation (Castle, 2015) of the European Union's Habitat Directive (Epstein et al, 2016).Third, in every country, whether wolves are legally protected or not, there is a high rate of human taking by vehicle strikes, livestock depredation control and poaching (Boitani, 2003;Liberg et al, 2012;Ciucci, 2015;Von Rushkowski, 2016).Even in the European Union, wolf protection is weakly enforced (Sazatornil et al, 2016).…”
Section: Wolf Recolonization Issuesmentioning
confidence: 99%
“…If the only place wolves can live with minimal conflict with humans is in wild lands, where are there sufficient wild lands that are still wolffree?Wild lands can be considered any extensive area undeveloped and relatively uninhabited by humans.There is necessarily some variation and subjectivity in considering where such areas suitable for wolves exist because the region surrounding many suitable wild lands would sustain conflict from wolves dispersing from them.The degree of conflict and the tolerance of local citizens will vary by locale.In Europe, that will depend considerably on the culture of each individual nation.How many of the 10,000 wolves Germany might be capable of supporting (Fechter and Storch, 2014) will it tolerate? In the U.S., estimates are that part of the southern Rocky Mountains could sustain a population of more than 1000 wolves (Carroll et al, 2003).In the Central U.S., a habitat-suitability study suggested that about 42% of the region (primarily Texas north through North Dakota) was suitable for wolves (Smith et al, 2015).However, those studies did not explicitly consider such negative factors as potential for depredation on livestock and other conflicts with humans, as well as local public attitudes toward wolves.The importance of these factors can be seen in the latter study's conclusion that substantial parts of North and South Dakota were deemed suitable even though wolves have been unable to recolonize them from Minnesota for decades because of poaching (Licht and Fritts, 1994).…”
Section: The Challenges Of Wolf Conservationmentioning
confidence: 99%
“…In western Poland the loss of any individual has been thought to influence the survival of the pack or interrupt colonization of adjacent areas (Jędrzejewski et al., ). Species distribution models have shown that human factors, especially road density and culling might limit the further spread of the species in Germany (Fechter & Storch, ) (Table ). The connectivity of the Central European Lowland population with neighbouring populations is still weak and currently restricted to occasional gene flow from the Baltic population (Kaczensky et al., ).…”
Section: The Main Threats To Wolf Populations In Europementioning
confidence: 99%